Patient Safety in Hysteroscopic Procedure - Wachyu Hadisaputra; Cindikia Ayu Sholekha Hani; Nidya Annisa Putri (Wolters Kluwer Medknow Publications, 2022)
This article aims to explain about outpatient hysteroscopy, where this procedure is currently being carried out. However, this procedure is also widely chosen by patients, because of its convenience, fast procedure, minimal complications, and of course more economical than day-case hysteroscopy. Before taking the procedure, it is important to explain to the patient about the disease, therapy, and the procedure to be carried out. Consent needs to be obtained voluntarily. We searched related publications using "patient safety" and "office hysteroscopy" and "informed consent" and "medical procedure" and "patient safety" and "injury" and "operative hysteroscopy" as keywords. This search had considered articles that had been published between 2002 and 2021. The conclusion from this library is that patient's convenient and safety is the top priority of outpatient hysteroscopy. Outpatient hysteroscopy showed higher satisfaction results than day-case hysteroscopy. Because it is more comfortable, faster, patients can immediately return to their activities and of course more efficient.